Teaching with Integrity in Mind - Burke, Kathleen (Canadian Perspectives on Academic Integrity, 2021)
An unanticipated move to remote teaching and learning in post-secondary institutions in March 2020 in response to the pandemic, left many of us scrambling to adapt our course content, teaching practices, and assessments to the online environment. On top of this, we, as educators, began to grapple with questions and realities regarding how the online landscape presented new challenges and opportunities related to academic integrity. Whatever academic integrity vulnerabilities and concerns that existed in our face-to-face offerings amplified when we went remote leaving many of us to implement makeshift adjustments to our courses and assessments to ‘close the holes.’ Academic integrity, however, should be built into curriculum development and teaching pedagogy rather than a situational response. Such an approach ensures that all aspects of instruction and assessment arc toward supporting student learning and promoting instructor and student fairness, honesty, trust, and responsibility (ICAI, 2021). This session outlines how an instance of student misconduct early in my academic career resulted in a journey to learn more about why students engage in dishonesty, strategies to better support student learning, and practices to cultivate an educational experience that seeks to model the values of academic integrity.